Effects of Shot-Peening and Stress Ratio on the Fatigue Crack Propagation of AL 7475-T7351 Specimens - Ferreira, Natália (2018)
Shot peening is an attractive technique for fatigue enhanced performance of metallic components, because it increases fatigue crack initiation life prevention and retards early crack growth. Engineering design based on fatigue crack propagation predictions applying the principles of fracture mechanics is commonly used in aluminum structures for aerospace engineering. The main purpose of present work was to analyze the effect of shot peening on the fatigue crack propagation of the 7475 aluminum alloy, under both constant amplitude loading and periodical overload blocks. The tests were performed on 4 and 8 mm thickness specimens with stress ratios of 0.05 and 0.4. The analysis of the shot-peened surface showed a small increase of the micro-hardness values due to the plastic deformations imposed by shot peening. The surface peening beneficial effect on fatigue crack growth is very limited; its main effect is more noticeable near the threshold. The specimen’s thickness only has marginal influence on the crack propagation, in opposite to the stress ratio. Periodic overload blocks of 300 cycles promotes a reduction of the fatigue crack growth rate for both intervals of 7500 and 15,000 cycles.